Epigallocatechin-3-gallate Mo nanoparticles (EGM NPs) efficiently treat liver injury by strongly reducing oxidative stress, inflammation and endoplasmic reticulum stress - Yang, Yunrong; Liu, Min; Zhao, Tianjiao; Chen, Qiaohui; Yang, Yuqi; Wang, Shuya; Zhang, Jinping; Deng, Guiming; Sun, Kewei; Nan, Yayun; Cao, Ke; Ai, Kelong; et al. (Frontiers in Pharmacology, 2022)
Drug-induced liver injury (DILI) is a serious clinical disease associated with reactive oxygen species (ROS) burst and subsequent inflammatory responses. Here, we developed a molybdenum (Mo) -based nanoparticles, EGM NPs, and demonstrated that EGM NPs treated acetaminophen (APAP)-induced DILI by scavenging ROS and modulating inflammation. EGM NPs exhibited multi-enzymatic activity and scavenged various ROS. At the cellular level, EGM NPs can effectively eliminate ROS, inhibit endoplasmic reticulum (ER) stress, reduce cell apoptosis, and decrease inflammatory factors. In vivo studies also showed that EGM NPs can treat APAP-induced DILI, successfully reducing the levels of liver function indicators in mice with liver injury and reducing the area of hepatocyte necrosis in the liver. EGM NPs also reduced the infiltration of macrophages in the liver, reduced the production of pro-inflammatory factors, and inhibited the expression levels of NOS2 and MPO, showing a certain anti-inflammatory effect. Collectively, our findings suggest that EGM NPs-based nanotherapeutic is a novel strategy for the treatment of DILI.